2013
DOI: 10.1007/978-3-642-40498-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Diversity – The Impact of Personality on Technology Acceptance

Abstract: Abstract. Technology is becoming increasingly automated, aiming to ease the life of its users. However, besides the advantages of this trend, users are also faced with increasing risks, e.g., regarding their privacy. Examples are seamless online payments that come with the requirement to provide sensitive, e.g., credit card information, or social networks trying to elicit private information for its users. Research on technology acceptance identified two important factors for the individual decision to accept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Dispositional trust represents an individual's general propensity to trust automation and/or humans across various contexts and circumstances [18]. Several studies have found that individuals with higher dispositional trust tend to place higher trust in automated systems [2,33,45]. However, these studies did not specify whether dispositional trust in automation and dispositional trust in humans would have similar effects on human-agent trust.…”
Section: Personal Influences: Empirical Gaps In Human-agent Trustmentioning
confidence: 74%
“…Dispositional trust represents an individual's general propensity to trust automation and/or humans across various contexts and circumstances [18]. Several studies have found that individuals with higher dispositional trust tend to place higher trust in automated systems [2,33,45]. However, these studies did not specify whether dispositional trust in automation and dispositional trust in humans would have similar effects on human-agent trust.…”
Section: Personal Influences: Empirical Gaps In Human-agent Trustmentioning
confidence: 74%
“…However, as there is great diversity in reactions to many different technologies with different functions [13], introducing new technologies to fit people's need and be accepted is very challenging. The diverse reactions may come from the difference in individual's personality, environment, culture values and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…[13]- [14], [19]). The reason to examine personality traits in the study of technology acceptance is because the basic concept underlying the model places significant focus on individual's reactions [20] in which personality traits is expected to play an important role in influencing the decision to accept the technology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations